Long Lines at Disney World Reduced by Sunstroke! or Can International Law Control Climate Change? - Jurgielewicz, Lynne (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 1991)
In the course of a meeting held in La Malbaie (Québec, Canada) on August 5th to 7th, 1990, thirty european, north-american and african jurists and economists exchanged ideas on the evolution of international economic law.This first colloquium organised by the SDIE (Canada) in cooperation with the SDIE (France) covered historical, theorical, practical and ethical aspects of this sector of law which covers the organisation of trade and production, monetary and financial relations, international trade law, resources management and environmental protection.The present document reproduces the texts submitted by the speakers in their original language. The first two papers aim at giving a general perspective of the variables of International Economic Law. The following papers focus on specific areas of international economic law where changes are taking place.